Moving beyond the stage: how characteristics at diagnosis dictate treatment and treatment-related quality of life year losses for women with early stage invasive breast cancer. (4th July 2021) - Saxby, Karinna; Nickson, Carolyn; Mann, G Bruce; Park, Allan; Bromley, Hannah; Velentzis, Louiza; Procopio, Pietro; Canfell, Karen; Petrie, Dennis
ABSTRACT: Background :Although evaluations of breast cancer screening programs frequently estimate quality-adjusted life-year (QALY) losses by stage, other breast cancer characteristics influence treatment and vary by mode of detection – i.e. whether the cancer is detected through screening (screen-detected), between screening rounds (interval-detected) or outside screening (community-detected). Here, we estimate the association between early-stage invasive breast cancer (ESIBC) characteristics and treatment-related QALY losses. Methods :Using clinicopathological and treatment information from 675 women managed for ESIBC, we estimated the average five-year treatment-related QALY loss by detection group. We then used regression analysis to estimate the extent to which known cancer characteristics and the detection mode, are associated with treatment and treatment-related QALY losses. Results :Community-detected cancers had the largest QALY loss (0.76 QALYs [95% CI 0.73;0.80]), followed by interval-detected cancers (0.75 QALYs [95% CI 0.68;0.82]) and screen-detected cancers (0.69 QALYs [95%CI 0.67;0.71]). Adverse prognostic factors more common in community-detected and interval-detected breast cancers (large tumours, lymph node involvement, high grade) were largely associated with QALY losses from mastectomies and chemotherapy. Receptor-positive subtypes, more common in screen-detected cancers, were associated with QALY losses related to endocrine therapy. Conclusions :The associations between ESIBC characteristics and treatment-related QALY losses should be considered when evaluating breast cancer screening and treatment strategies.